The impact of regulations on compliance costs, risk-taking, and the reporting quality of the EU banks - Poshakwale, Sunil S.; Aghanya, Daniel; Agarwal, Vineet (Elsevier, 2019)
The paper examines how the Statutory Audit and Corporate Reporting Directives (SACORD) affect the compliance costs, risk taking and quality of financial reporting of the EU banks. Using a natural experiment, we find that post SACORD, both compliance costs and risk taking increase significantly. However, the implementation of additional regulations seems to be effective in terms of improved quality of financial reporting. When we analyse the impact by size, we find that smaller banks face disproportionately higher increase in compliance costs while larger banks seem to engage in greater risk taking.
Keywords: Financial regulation; Transparency; Financial system; Financial stability; Difference-in-differences